2021
DOI: 10.1080/17480272.2021.1925963
|View full text |Cite
|
Sign up to set email alerts
|

Selected previous findings on the factors influencing the gluing quality of solid wood products in timber construction and possible developments: A review

Abstract: Various factors affect the bonding quality of elements used for timber construction. This review includes literature studies and personal experiences related to relevant technological variables defining glue bond performance in glue-laminated timber elements during their service life. The gluing of hardwood species receives special focus as it is considered by the industry to be the most challenging process for implementation. In particular, the effects of wood species, type of adhesive, glued-wood surface qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
0
21
0
2
Order By: Relevance
“…A major issue that poses problems for successfully bonding high-density timbers is that their elevated mechanical resistance leads to a lower rate of wood failure [22]. Structural adhesives are generally assumed to be stronger than the substrate, and bond quality tests (including AS/NZS 1328.1:1998 [3]) often judge performance on the percentage of wood versus adhesive failure.…”
Section: Elevated Strength and Mechanical Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A major issue that poses problems for successfully bonding high-density timbers is that their elevated mechanical resistance leads to a lower rate of wood failure [22]. Structural adhesives are generally assumed to be stronger than the substrate, and bond quality tests (including AS/NZS 1328.1:1998 [3]) often judge performance on the percentage of wood versus adhesive failure.…”
Section: Elevated Strength and Mechanical Resistancementioning
confidence: 99%
“…Table 1 illustrates the higher shrinkage rate (from unseasoned to 12% moisture content) and unit movement values (with each 1% change of moisture content) of spotted gum and Darwin stringybark compared to two other lower-density commercial timbers commonly used in glulam. When compared to other species, this higher dimensional movement combined with a higher modulus of elasticity of the timber likely creates a greater propensity for the glulam to delaminate due to high stresses developing at the glue-line and causing the sawn laminates to separate [13,16,18,22]. However, attempts to dimensionally stabilise spotted gum and Darwin stringybark timber through the use of hydrophobic agents and coatings have not yet been successful in achieving acceptable glue line delamination results in accordance with AS/NZS 1328.1:1998 [3,9].…”
Section: Higher Dimensional Movementmentioning
confidence: 99%
“…The test method and subsequent use of the wood product are also crucial. There are numerous other factors that affect wood bonding, which are discussed in the literature [ 20 , 21 , 22 , 24 , 25 , 26 ].…”
Section: Bonding Woodmentioning
confidence: 99%
“… The penetration of water-soluble adhesive is altered because acetylated wood absorbs less water. Swelling produced by cold curing adhesives absorbing water can cause cracks [ 25 , 80 ], which would be decreased on acetylated wood. On the other hand, the reduced penetration may have a negative impact on mechanical adhesion.…”
Section: Bonding Acetylated Woodmentioning
confidence: 99%
“…On beech surface bonding, references [6][7][8] showed that individual adhesive systems (partly without proof of applicability for hardwood) can fulfil the normative requirements for delamination resistance, but their results were, at the same time, dependent on a large number of parameters. Main influencing factors are the effects of the wood species and wood modifications, the type of adhesive and its processing, the quality of the bonding surface, and varying climatic conditions during production and in the use phase [9,10]. Various one-component polyurethane and two-component aminoplast adhesive systems used for finger-jointing beech and oak showed negative results compared to the normative requirements for delamination resistance [6].…”
Section: Introductionmentioning
confidence: 99%